Cyber Poskamling Sebagai Implementasi Resiprokal Al-Qur’an Terhadap Kontra Cyber Radicalism: Analisis Makna “Ta’āwun” Q.S. Al-Maidah Ayat 2 - Alim, Khozinul (At-Tahfidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2022)
Social media is now an inseparable part of human life, along with technological advances, social media has also experienced a very significant development. In addition to producing positive effects with all the facilities offered, the development of social media also produces negative effects that must be watched out for. One of them is the birth of radical content. Departing from this problem, the author conducted this research in the hope of contributing to the prevention of cases of the spread of radical content in cyberspace (cyber radicalism) by taking inspiration from. Q.S. al-Maidah [5]: 2. This paper departs from two big questions, namely: first, how is the interpretation and contextualization of Q.S. al-Maidah [5]: 2 as the basic concept of reciprocal al-Qur'an?, secondly how is the implementation of Q.S. al-Maidah [5]: 2 as inspiration from cyber poskamling?. The method used in this research is the library study method. From the results of this study, the authors conclude that: (1) First, Q.S. Al-Maidah explains the prohibition of repaying evil with the same evil on the basis of revenge, on the contrary the verse commands to help each other in doing good. In the current post truth era, the verse can be understood as a call to humans to work hand in hand to counteract radical content (cyber radicalism) that creates divisions among society; and (2) concrete steps of implementing Q.S. al-Maidah [5]: 2 is by promoting cyber poskamling as one of the efforts to fight the attacks of radical content circulating in cyberspace, in addition to the government and its ministries making policies through presidential regulations and ministerial regulations, as well as law enforcement officers taking preventive actions. By establishing a cyber patrol, the public must also play an active role by establishing a cyber poskamling and reporting to the authorities if they find content or websites that are indicated to contain radical content and then legal action is taken by the competent authorities in accordance with applicable laws.